Factors associated with the availability and affordability of essential cardiovascular disease medicines in low- and middle-income countries: A systematic review. - Ali Lotfizadeh; Benjamin Palafox; Armin Takallou; Dina Balabanova; Martin McKee; Adrianna Murphy (PLOS Global Public Health)
Despite their potential to prevent or delay the onset and progression of cardiovascular disease (CVD), medicines for CVD remain unavailable and unaffordable to many in low- and middle-income countries (LMICs). We systematically reviewed the literature to identify factors associated with availability and affordability of CVD medicines in LMICs. A protocol for this study was registered on the PROSPERO register of systematic reviews (CRD42019135393). We searched Medline, EMBASE, Global Health, Cumulative Index to Nursing and Allied Health Literature, EconLit, Social Policy and Practice, and Africa Wide Information for studies analyzing factors associated with the presence of medicines (availability) or the price of these medicines as it relates to ability to pay (affordability) in LMICs. We performed a narrative synthesis of the results using an access to medicines framework that examines influences at different levels of the health system. We did not conduct a meta-analysis because of the differences in analytic approaches and outcome measures in different studies. The search was conducted in accordance with PRISMA guidelines. Of 43 studies meeting inclusion criteria, 41 were cross-sectional. Availability and affordability were defined and measured in different ways. A range of factors such as sociodemographic characteristics, facility tier, presence of medicines on national essential medicine lists, and international subsidy programs were examined. The studies had variable quality and findings were often inconsistent. We find gaps in the literature on factors associated with availability and affordability of CVD medicines, particularly at the health program level. We conclude that there is a need for experimental and quasi-experimental studies that could identify causal factors and effective responses. Such studies would help further our understanding of how complex multifactorial influences impact these outcomes, which could inform policy decisions. Along with this, greater standardization of definitions and measurement approaches of availability and affordability are needed to allow for more effective comparisons.